EL EFECTO DE LAS CADENAS DE DISTRIBUCIÓN EN LA RENTABILIDAD DE LAS AVÍCOLAS EN LA CIUDAD DE CATACOCHA, CANTÓN PALTAS, PROVINCIA DE LOJA, PERIODO ENERO-DICIEMBRE 2017 - Agila Cuenca, Delia Andrea (2018)
Currently at the local and regional level poultry production and marketing has grown significantly, giving a new working approach to families with low economic resources. But one of the problems faced by people engaged in this activity is the lack of preparation to carry an adequate commercialization; In light of this, the present research work called "the effect of the distribution chains on the profitability of poultry in the city of Catacocha, canton of the province of Loja, January-December 2017", whose general objective was to analyze the chains of distribution and its effect on the profitability of poultry in the city of Catacocha, Paltas canton, Loja Province; through a quantitative analysis of sales, during the period January-December 2017. The aforementioned research was carried out based on the owners of the most important poultry beds in the town, as well as the general population of the city of Catacocha. We used the scientific method is its different expressions. Likewise, the technique applied to collect the data was, the survey and the interview, with which the following results were obtained: more than half of the population (61.59%) consumed an average of 1 to 4 pounds. of chicken every two days a week, 58.41%, of the plaintiffs of chicken meat bought in the organized market, while 30.16% do it in the Casa del Pollo and only 3.81% acquires the product in retail stores; within the analyzed beds it could be established that they present an indirect distribution channel, this channel is constituted by the producer, the final consumer and at least by a level of intermediaries; When the financial analysis was applied, it was determined that the liquidity index is adequate, that the return on fixed assets is slow and the return on equity remains within the optimum parameters for the growth of poultry.